CONFORMITY IN THE DECISION TO BUY BIKE ACCESSORIES AND SPARE PARTS FOR ADULT AGE CYCLISTS - Kirana, Garda Sukma; Firdausi, Naura Nuha; Aziz, Dzulchilda Khoirunnisa; Noveni, Nia Anggri (Psychosophia: Journal of Psychology, Religion, and Humanity, 2024)
The current needs of cyclists, which have now become part of their lifestyle, are accessories and spare parts. One of the reasons someone decides to buy something is due to the influence of conformity. The purpose of this study is to predict the contribution of conformity behavior to the decision to purchase bicycle accessories and spare parts. This research uses a quantitative method with a simple regression analysis. The scales used are the conformity scale and the purchase decision scale. The sampling technique used in this is the purposive sampling technique. The population in this study consists of adult cyclists (21–60 years old), for a total of 83 participants. Based on the analysis of data collected from the conformity scale and purchase decision scale, then processed using SPSS version 26, it was found that the significance value of conformity and purchase decision is 0.00 (p= < 0.05), which means conformity significantly influences purchase decisions. However, this influence occurs negatively. Meanwhile, the contribution of conformity to purchase decisions is 16.9%. Based on the research results, it is shown that adult cyclists exhibit conformity behavior, and this conformity behavior negatively influences the decision to purchase bicycle accessories and spare parts. This finding is noteworthy because conformity is commonly found in adolescents, while adulthood is generally referred to as "trial and error" behavior, but this time conformity behavior is found in adults. The reason conformity only slightly influences purchase decisions may be because there are still many other factors influencing purchase decisions, such as self-concept, product quality, product branding, lifestyle, attitudes or evaluations of products, and income.